A challenging breast cancer type; Differentiation to neuroendocrine tumors - Yıldız, Ömer Serdar; Başak, Fatih (Journal of Surgery and Medicine, 2017)
Aim: Neuroendocrine type breast carcinomas are rarely observed. Most of these tumors are seen as cell-differentiated neuroendocrine breast carcinoma but with all this infrequency, there is also a rarer type which is called as pure neuroendocrine breast carcinoma. The common locations for neuroendocrine tumors are lung and gastrointestinal system (stomach and pancreas). Although estimations vary, the annual incidence of clinically significant neuroendocrine tumors is approximately 6.5-5 per 500,000; two thirds are carcinoid tumors and one third are other neuroendocrine tumors. The estimated prevalence is 35 per 100,000. In this article, we analyze the patients admitted with breast problems and had the diagnosis of breast cancer with neuroendocrine differentiation or purely neuroendocrine tumor. Methods: Retrospective cohort study is designed to review neuroendocrine breast cancer patients. Female patients with pathological examination which have neuroendocrine components in neoplasm were reviewed. Demographics, preoperative imaging, diagnostic evaluations, operation and pathological examination records of patients were recorded. Results: Neuroendocrine breast cancer was observed in 11 patients in study period. All patients received standard therapy like non-specific breast cancer. Only two of 11 patients (18%) were diagnosed with neuroendocrine differentiation in preoperative period by biopsy. One patient received neoadjuvant treatment. Modified radical mastectomy was performed in eight patients (72.8%). Breast conserving surgery was performed in remaining three patients. Conclusion: Neuroendocrine breast cancer is rare entity, and diagnose at preoperative period may be challenging. In most cases the correct diagnosis is made after proper examination of the postsurgical specimen. Future studies for specific treatments would be of interest.